Biological composition, efficacy, and primary efficacy endpoint of SARS-CoV-2 vaccines; a special communication - Imran Ishaque; Muhammad Muhib; Omer Bin Khalid Jamil (Journal of the Pakistan Medical Association, 2022)
Severe acute respiratory syndrome coronavirus 2 was first reported in Wuhan, China, in late December 2019 and rapidly spread out globally, affecting 130 million individuals and starting a global pandemic. An efficacious vaccine is considered an essential tool to reduce mortality and morbidity rate related to the pandemic. Nine different vaccine candidates announced the efficacy results of their respective phase 3 trial testing up till January 2021. By the end of June 2021, the administration of seven different vaccines started under the supervision of the World Health Organisation. The current article was planned to discuss the biological composition, efficacy and primary efficacy endpoint described in literature, and to identify the factors that could affect vaccine efficacy and vaccine coverage. Key Words: SARS-CoV-2 vaccine, Efficacy, Vaccine coverage, Efficacy endpoint, Factors.